TOOLS FOR IMPROVING OPERATIONAL RISK MANAGEMENT IN AGRICULTURE - & et al., Rossinskaya (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The agricultural sector is most subject to the influence of risk factors. This might be explained by the fact that the efficiency and the output of agricultural production depends not only on invested labor and funds, but also on climatic, weather, environmental conditions, natural disasters. In this regard, the development of theoretical foundations of operational risk management in agriculture is highly relevant. The objective of our study was to develop measures to improve the methods of risk assessment and operational risk management at the level of agricultural enterprises, taking into account the requirements of environmental management and environmental protection. The article discusses the conditions and features of agricultural production at the present stage of economic development, gives a comparative description of various sectors of the economy by the presence of risk factors and proposes methods for operational risk management in the agro-industrial complex. An risk management algorithm for agricultural enterprises has been developed.